2020
DOI: 10.1186/s40246-020-00268-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of non-invasive prenatal served as a first-tier screening test for trisomy 21, 18, 13 and sex chromosome aneuploidy in a pilot city in China

Abstract: Background: Cell-free fetal DNA (cffDNA) has opened up new approaches for non-invasive prenatal testing (NIPT), and it is often used as the second-tier test for high-risk pregnant women in detecting trisomy (T) 21, T18, and T13 after serum biochemistry screening. This study aims to discuss the clinical performance of NIPT as an alternative first-tier screening test for pregnant women in detecting T21, T18, T13, and sex chromosome aneuploidies (SCAs) in China. Methods: A total of 42,924 samples were recruited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 39 publications
2
46
1
Order By: Relevance
“…Serological screening for trisomies based on maternal serum-free β-human chorionic gonadotrophin (β-HCG), pregnancy-associated plasma protein-A (PAPP-A), and αfetoprotein (AFP) levels is still widely used in China. These biochemical markers, combined with maternal age, are usually used for screening for Down syndrome and can achieve a detection rate of 70-80% but a PPV of almost 10% [19]. Compared with NIPT for detection of T21 in our study, the sensitivity and specificity of serological screening seemed unsatisfactory.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Serological screening for trisomies based on maternal serum-free β-human chorionic gonadotrophin (β-HCG), pregnancy-associated plasma protein-A (PAPP-A), and αfetoprotein (AFP) levels is still widely used in China. These biochemical markers, combined with maternal age, are usually used for screening for Down syndrome and can achieve a detection rate of 70-80% but a PPV of almost 10% [19]. Compared with NIPT for detection of T21 in our study, the sensitivity and specificity of serological screening seemed unsatisfactory.…”
Section: Discussioncontrasting
confidence: 56%
“…A recent study of 31,515 singleton pregnancies in southeastern China showed a high sensitivity and specificity for T21, T18, T13, and SCAs, and the positive predictive values were high for T21 and T18 and moderate for T13 and SCAs [16]. Therefore, NIPT has been implemented into public healthcare systems as either a first-line test or a supplement to the existing prenatal screening; more and more pregnant women are willing to choose NIPT [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…There is a situation in which a chromosomal abnormality that occurs only in the placenta but not in the fetus is known as CPM. Therefore, collecting placental tissue for further verification is a critical part of confirming CPM, which is reported in Liu’s latest article [ 18 ]. In this study, no placental tissue was obtained for verification, which was a limitation of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Samples were processed, and plasma was shipped frozen when necessary. Trisomies 13,18, and 21 were reported as well as other chromosomal aneuploidies. Cell-free DNA extraction, library construction, sequencing, and bioinformatics analysis were performed according to a previous study.…”
Section: Sample Preparation and Sequencingmentioning
confidence: 99%
“…In Europe, Belgium, and the Netherlands have begun offering NIPT for all pregnant women, while numerous other countries offer NIPT for women deemed higher risk after first-tier screening. 2,3 Research shows that NIPT could increasingly be implemented as a first-tier screen for all pregnant women and many countries including Canada (http://pegasus-pegase.ca/), are exploring this option 1,[4][5][6] Barriers to increased implementation of NIPT center on costs (for individuals or healthcare systems), patient and practitioner education, as well as various social and ethical implications. 1,7,8 NIPT is seen as beneficial, as it enhances reproductive autonomy but also problematic, as it can, for example, have negative impact on disability rights.…”
Section: Introductionmentioning
confidence: 99%